Diagnostic and Therapeutic Laparoscopy for Abdominal Trauma: A Single Surgeon’s Experience at a Level I Trauma Center - Hancheol Jo; Dong Hun Kim (Journal of Trauma and Injury)
Purpose Laparoscopy has various advantages over laparotomy in terms of postoperative recovery. The number of surgeons using laparoscopy as a diagnostic and therapeutic tool in abdominal trauma patients is increasing, whereas open conversion is becoming less common. This report summarizes a single surgeon’s experience of laparoscopy at a level I trauma center and evaluates the feasibility of laparoscopy as a diagnostic and therapeutic tool for abdominal trauma patients. Methods In total, 30 abdominal trauma patients underwent laparoscopy by a single surgeon from October 2014 to May 2020. The purpose of laparoscopy was categorized as diagnostic or therapeutic. Patients were classified into three groups by type of surgery: total laparoscopic surgery (TLS), laparoscopy-assisted surgery (LAS), or open conversion (OC). Univariate analysis was performed to determine the advantages and disadvantages. Results The mechanism of injury was blunt in 19 (63.3%) and penetrating in 11 patients (36.7%). Eleven (36.7%) and 19 patients (63.3%) underwent diagnostic and therapeutic laparoscopy, respectively. The hospital stay was shorter for patients who underwent diagnostic laparoscopy than for those who underwent therapeutic laparoscopy (5.0 days vs. 13.0 days), but no other surgical outcomes differed between the groups. TLS, LAS, and OC were performed in 12 (52.2%), eight (34.8%), and three patients (13.0%), respectively. There was no significant difference in morbidity and mortality among the three groups. Conclusions Laparoscopic surgery for selected cases of abdominal trauma may be feasible and safe as a diagnostic and therapeutic tool in hemodynamically stable patients due to the low OC rate and the absence of fatal morbidity and mortality.